Odpowiedzi

Najlepsza Odpowiedź!
2010-04-07T13:01:36+02:00

c = 6*(√2 + 1)
zatem r = c :2 = 3*(√2 + 1)
a ponieważ trójkąt jest prostokątny równoramienny, zatem
h = r = 3*(√2 + 1)
l = 3*(√2 +1)*√2
mamy
V = (1/3)π r² h = (1/3)*π *[3*(√2 +1)]²* 3*(√2 +1) =
= 9π*(√2 +1)²*(√2 +1)
Pc = Pp + Pb = π r² + π r l = π {3*(√2+1)]² + π*3*(√2 +1)*3*(√2+1)*√2=
= π *9*(√2 +1)²*[1 + √2]
zatem
V : Pc = 1
2010-04-07T13:04:44+02:00
DANE /patrz zalacznik/
2r= 6(√2+1)cm.
OBL
V:Sc

r= 3(√2+1)
jezeli kat wierzcholkowy 90°
to h=r
k=r√2 /przekatna kwadratu o boku r/

V=1/3πr²*h=1/3πr³
Sc=πr²+πrk=πr(r+r√2 )=πr²(1+√2)
V:Sc=1/3r/(1+√2)=1/3*3(√2+1)/(1+√2)=(√2+1)/(1+√2)=1

ODP
V:Sc=1

pozdrawiam

Hans